2009
DOI: 10.2165/00007256-200939070-00003
|View full text |Cite
|
Sign up to set email alerts
|

Physical Attributes, Physiological Characteristics, On-Court Performances and Nutritional Strategies of Female and Male Basketball Players

Abstract: This article reviews a series of studies (n = 51) examining physical attributes, physiological characteristics, on-court performances and nutritional strategies of female and male elite basketball players. These studies included relevant information on physical and physiological variables, such as height, weight, somatotype, relative size, aerobic profile, strength, anaerobic power, agility and speed. Six main findings emerged from our review: (i) differences in physical attributes exist among playing position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
277
2
34

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(324 citation statements)
references
References 43 publications
11
277
2
34
Order By: Relevance
“…The difference in relative intensity displayed by referees and players therefore increases as matches' progress, with the greatest discrepancy occurring in the final quarter. It is also apparent that the relative HR values recorded in this study are higher than those reported in an international women's tournament by Leicht (2008), thereby suggesting that the physiological strain imposed by officiating may be greater in male tournaments, possibly dues to the greater physiological capacities of elite male players (Ziv and Lidor, 2009). …”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The difference in relative intensity displayed by referees and players therefore increases as matches' progress, with the greatest discrepancy occurring in the final quarter. It is also apparent that the relative HR values recorded in this study are higher than those reported in an international women's tournament by Leicht (2008), thereby suggesting that the physiological strain imposed by officiating may be greater in male tournaments, possibly dues to the greater physiological capacities of elite male players (Ziv and Lidor, 2009). …”
Section: Discussioncontrasting
confidence: 46%
“…Given that Ziv & Lidor (2009) have reported that elite male basketball players display increased aerobic capacity values compared to female players, it is by no means certain that the physiological responses in a group of male referees officiating an international male tournament will be similar to those in a group of (predominantly) male referees officiating a female tournament. This study examined physiological responses in a group of international referees during match play at a major international basketball championship to determine whether physical activity levels were maintained throughout the course of matches.…”
Section: Introductionmentioning
confidence: 99%
“…According to several time-motion studies, these skills are basic in high level basketball games, as they are involved in about a third of all game actions (Abdelkrim, Castagna, Jabri, Battikh, Fazaa, & Ati, 2010;Abdelkrim, El Fazaa, & El Ati, 2007;Narazaki, Berg, Stergiou, & Chen, 2009). So, achieving good performances in these variables is part of any basketball training program from an early age (Abdelkrim et al, 2010;Castagna, Abt, Manzi, Annino, Padua, & D'Ottavio, 2008;Castagna, Manzi, D'Ottavio, Annino, Padua, & Bishop, 2007;Korkmaz & Karahan, 2012;Marzilli, 2008;Ziv & Lidor, 2009). The ability to repeat sprints (RSA) has been much studied in the literature because of its relevance in team sports (Bishop, Girard, & MendezVillanueva, 2011;Caprino, Clarke, & Delextrat, 2012;Castagna et al, 2008;Dawson, 2012;Wong, Gar Sun, & Smith, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ben Abdelkrim et al (2007) examined internal load, expressed by average heart rate, and found that 91± 2% of peak heart rate (HR peak ) of players (national Tunisian U19 team) was achieved during a warm up match. Ziv and Lidor (2009) stated that 86.20 ± 5.30% of HR peak was achieved during the first half and that 86.70 ± 4.30% of HR peak was achieved during the second half of the warm up match (U18 category). Average heart rate, measuring from 87 to 91% of HR peak, was examined in studies that focused on a cohort of top senior basketball players (Matkovič R. B., Matkovič B., & Knajz, 2005;McInnes, Carlson, Jones, & McKenna, 1995;Montgomery, Pyne, & Minanhan, 2010).…”
Section: Introductionmentioning
confidence: 99%